Pengaruh Dosis Pemupukan terhadap Pendapatan Usahatani Padi pada Lahan Marginal di Kecamatan Pademawu Kabupaten Pamekasan - MOHAMMAD SHOIMUS SHOLEH; DEWO RINGGIH (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Effect of Fertilizer Dosage on Income of Rice Farming at Marginal Land in Pademawu District, Pamekasan Regency In carrying out farming activities, production factors, especially the use of fertilizers, have an important role to increase the production and income of farmers, especially rice farming on marginal land. The main problem is how to combine the use of organic and inorganic fertilizers that highest income. The method used is the analysis of Multiple Linear Regression and Revenue Cost Rasio (R/C) value to determine the level of efficiency of each fertilizer treatment. The cost of using organic and inorganic fertilizers has a significant and significant effect on the increase in income of rice farming. The highest income was on treatment 9 with the use of urea 200 kg ha-1 + NPK 200 kg ha-1 + organic 1,000 kg ha-1 with R/C value of 1.34 with an increase of 32.77% compared to without the treatment of organic fertilizer.